2020
DOI: 10.30659/e.5.2.304-321
|View full text |Cite
|
Sign up to set email alerts
|

EFL teachers� beliefs and practices about digital learning of English

Abstract: The last two decades have been the witness of many studies reporting the disparity between EFL teachers� beliefs and practices in technology integration around the world. Notwithstanding the enormous studies on EFL teachers� beliefs and perceptions of digital technology use for language classroom, the literature has still been silent on the relation between Indonesian EFL teachers� beliefs and practices. The present study thus sheds some light on 15 EFL teachers� beliefs and practices about digital learning of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 35 publications
(49 reference statements)
7
41
0
Order By: Relevance
“…The media used in English as Foreign Language classes has evolved in some countries, along with the development of technology. Some face to face classrooms are slowly progressing into online classes (Lee & Lee, 2019;Nugroho & Mutiaraningrum, 2020). Some previous studies have discussed this shift in various countries.…”
Section: Introductionmentioning
confidence: 99%
“…The media used in English as Foreign Language classes has evolved in some countries, along with the development of technology. Some face to face classrooms are slowly progressing into online classes (Lee & Lee, 2019;Nugroho & Mutiaraningrum, 2020). Some previous studies have discussed this shift in various countries.…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, this study revealed that teachers prepared learning materials and online assessments long days before their teaching schedule. This is supported by Nugroho and Mutiaraningrum (2020) and Nugroho, Ilmiani, and Rekha (2020) reporting that online learning consumes a lot of time to prepare the learning materials. Moreover, the unfamiliarity of using online learning platforms such as sending documents/files, creating tasks deadline, checking students' presence, submitting tasks, and archiving students' work becomes another great challenge for teachers in their online class (Sun et al, 2020).…”
Section: Discussionmentioning
confidence: 86%
“…Early studies have pointed out that if a change in classroom practice is the intended outcome, addressing the change in teachers' beliefs about the use of the provided technology is crucial (e.g., Ottenbreit-Leftwich et al, 2010;Palak & Walls, 2009). In this regard, recent studies conducted among English language teachers have found several insights: 1) teachers' content-specific pedagogical beliefs can be different, which, in turn, results in the various ways of utilizing the same type of technological tools (Ding et al, 2019), 2) EFL teachers commonly share positive views on the use of digital technology, but gender, age, and teaching experience cannot alter teachers' beliefs (Hol & Aydın, 2020), and 3) despite having adequate knowledge of technology use in teaching, teachers may still be hesitant and unable to use technology in their classroom practices due to inadequate training, resources, and facilities (Nugroho & Mutiaraningrum, 2020).…”
Section: Teachers' Beliefsmentioning
confidence: 99%